Preparation of anthracene-based tetraperimidine hexafluorophosphate and selective recognition of chromium(III) ions - Liu, Qing-Xiang; Yang, Feng; Zhao, Zhi-Xiang; Yu, Shao-Cong; Ding, Yue (Beilstein Journal of Organic Chemistry, 2019)
A novel anthracene-based tetraperimidine hexafluorophosphate 3 was prepared, and its structure was determined through X-ray analysis, HRMS as well as 1H and 13C NMR spectroscopy. In the cationic moiety of 3, two (N-ethylperimidinyl–C2H4)2NCH2– arms were attached to the 9- and 10-positions of anthracene. In addition, compound 3 was used as a chemosensor to research the ability to recognize Cr3+ through fluorescence and UV titrations, HRMS, as well as 1H NMR and IR spectroscopy. The results indicate that 3 is an effective chemosensor for Cr3+.
Keywords: chemosensor; chromium(III) ion; tetraperimidine

(untitled) - Lee, M. H.; Kim, J. S.; Sessler, J. L. (Chem. Soc. Rev., 2015)

(untitled) - Carter, K. P.; Young, A. M.; Palmer, A. E. (Chem. Rev., 2014)

(untitled) - Zhang, X.; Yin, J.; Yoon, J. (Chem. Rev., 2014)

(untitled) - Kim, H. N.; Ren, W. X.; Kim, J. S.; Yoon, J. (Chem. Soc. Rev., 2012)

(untitled) - Li, Z.; Yu, M.; Zhang, L.; Yu, M.; Liu, J.; Wei, L.; Zhang, H. (Chem. Commun., 2010)

(untitled) - Jiao, X.; Huang, K.; He, S.; Liu, C.; Zhao, L.; Zeng, X. (Org. Biomol. Chem., 2019)

(untitled) - Jiao, X.; Liu, C.; He, S.; Zhao, L.; Zeng, X. (Dyes Pigm., 2019)

(untitled) - Cheng, J.; Yang, E.; Ding, P.; Tang, J.; Zhang, D.; Zhao, Y.; Ye, Y. (Sens. Actuators, B, 2015)

(untitled) - Arakawa, H.; Ahmad, R.; Naoui, M.; Tajmir-Riahi, H.-A. (J. Biol. Chem., 2000)

(untitled) - Anderson, R. A. (Regul. Toxicol. Pharmacol., 1997)

(untitled) - Vincent, J. B. (Nutr. Rev., 2000)

(untitled) - Vincent, J. B. (Proc. Nutr. Soc., 2004)

(untitled) - Costa, M.; Klein, C. (Crit. Rev. Toxicol., 2006)

(untitled) - Dai, R.; Yu, C.; Liu, J.; Lan, Y.; Deng, B. (Environ. Sci. Technol., 2010)

(untitled) - Tang, Y.; Liu, L.; Zhang, Y.; Zhao, H.; Kong, L.; Gao, S. (New J. Chem., 2018)

(untitled) - Raju, V.; Selva Kumar, R.; Ashok Kumar, S. K.; Tharakeswar, Y.; Sahoo, S. K. (Inorg. Chem. Commun., 2019)

(untitled) - Wu, S.; Zhang, K.; Wang, Y.; Mao, D.; Liu, X.; Yu, J.; Wang, L. (Tetrahedron Lett., 2014)

(untitled) - Shahim, S.; Sukesan, R.; Sarangadharan, I.; Wang, Y.-L. (Sensors, 2019)

(untitled) - Yin, H.; Zhao, B.; Kan, W.; Liu, T.; Wang, W.; Yin, G.; Wang, L.; Gao, Y.; Wang, J. (Spectrochim. Acta, Part A, 2019)

(untitled) - Zhang, M.; Gong, L.; Sun, C.; Li, W.; Chang, Z.; Qi, D. (Spectrochim. Acta, Part A, 2019)

(untitled) - Sutariya, P. G.; Soni, H.; Gandhi, S. A.; Pandya, A. (J. Lumin., 2019)

(untitled) - Koonrugsa, N.; Fuangswasdi, S. (Spectrochim. Acta, Part A, 2019)

(untitled) - Zhang, T.; Mu, L.; She, G.; Shi, W. (J. Lumin., 2019)

(untitled) - Zhu, H.; Fan, J.; Wang, B.; Peng, X. (Chem. Soc. Rev., 2015)

(untitled) - Shirinfar, B.; Ahmed, N.; Park, Y. S.; Cho, G.-S.; Youn, I. S.; Han, J.-K.; Nam, H. G.; Kim, K. S. (J. Am. Chem. Soc., 2013)

(untitled) - Lim, N. C.; Pavlova, S. V.; Brückner, C. (Inorg. Chem., 2009)

(untitled) - Xu, M.; Wu, S.; Zeng, F.; Yu, C. (Langmuir, 2010)

(untitled) - Weerasinghe, A. J.; Schmiesing, C.; Varaganti, S.; Ramakrishna, G.; Sinn, E. (J. Phys. Chem. B, 2010)

(untitled) - Goswami, S.; Aich, K.; Das, S.; Das, A. K.; Sarkar, D.; Panja, S.; Mondal, T. K.; Mukhopadhyay, S. (Chem. Commun., 2013)

(untitled) - Mahato, P.; Saha, S.; Suresh, E.; Di Liddo, R.; Parnigotto, P. P.; Conconi, M. T.; Kesharwani, M. K.; Ganguly, B.; Das, A. (Inorg. Chem., 2012)

(untitled) - Liu, C.; Pan, J.; Li, S.; Zhao, Y.; Wu, L. Y.; Berkman, C. E.; Whorton, A. R.; Xian, M. (Angew. Chem., Int. Ed., 2011)

(untitled) - Choi, M. G.; Cha, S.; Lee, H.; Jeon, H. L.; Chang, S.-K. (Chem. Commun., 2009)

(untitled) - Sasakura, K.; Hanaoka, K.; Shibuya, N.; Mikami, Y.; Kimura, Y.; Komatsu, T.; Ueno, T.; Terai, T.; Kimura, H.; Nagano, T. (J. Am. Chem. Soc., 2011)

(untitled) - Zhang, L.; Lou, X.; Yu, Y.; Qin, J.; Li, Z. (Macromolecules, 2011)

(untitled) - Cao, X.; Lin, W.; He, L. (Org. Lett., 2011)

(untitled) - Zhang, H.; Sun, T.; Ruan, Q.; Zhao, J.-L.; Mu, L.; Zeng, X.; Jin, Z.; Su, S.; Luo, Q.; Yan, Y.; Redshaw, C. (Dyes Pigm., 2019)

(untitled) - Mabhai, S.; Dolai, M.; Dey, S. K.; Dhara, A.; Choudhury, S. M.; Das, B.; Dey, S.; Jana, A. (Spectrochim. Acta, Part A, 2019)

(untitled) - Hosseini, M.; Khoobi, M.; Tarasi, R.; Ganjali, M. R. (Res. Chem. Intermed., 2018)

(untitled) - Jang, H. J.; Kang, J. H.; Yun, D.; Kim, C. (J. Fluoresc., 2018)

(untitled) - Singh, J.; Kaur, V.; Singh, R.; Bhardwaj, V. K. (Spectrochim. Acta, Part A, 2018)

(untitled) - Miller, M. W.; Amidon, R. W.; Tawney, P. O. (J. Am. Chem. Soc., 1955)

(untitled) - Verlinden, K.; Ganter, C. (J. Organomet. Chem., 2014)

(untitled) - Pickering, A. L.; Seeber, G.; Long, D.-L.; Cronin, L. (CrystEngComm, 2005)

(untitled) - Upadhyay, Y.; Paira, P.; Ashok Kumar, S. K.; Choi, H.-J.; Kumar, R.; Sahoo, S. K. (Inorg. Chim. Acta, 2019)

(untitled) - Adhikari, S.; Ta, S.; Ghosh, A.; Guria, S.; Pal, A.; Ahir, M.; Adhikary, A.; Hira, S. K.; Manna, P. P.; Das, D. (J. Photochem. Photobiol., A, 2019)

(untitled) - Jin, H.; Xu, J.; Zhang, L.; Ma, B.; Shi, X.; Fan, Y.; Wang, L. (J. Solid State Chem., 2018)

(untitled) - Liu, Q.-X.; Yao, Z.-Q.; Zhao, X.-J.; Zhao, Z.-X.; Wang, X.-G. (Organometallics, 2013)

(untitled) - Goswami, S.; Hazra, A.; Chakrabarty, R.; Fun, H.-K. (Org. Lett., 2009)

(untitled) - Ulatowski, F.; Dąbrowa, K.; Bałakier, T.; Jurczak, J. (J. Org. Chem., 2016)

(untitled) - Arunkumar, E.; Ajayaghosh, A.; Daub, J. (J. Am. Chem. Soc., 2005)

(untitled) - Thordarson, P. (Chem. Soc. Rev., 2011)

(untitled) - Caballero, A.; Martínez, R.; Lloveras, V.; Ratera, I.; Vidal-Gancedo, J.; Wurst, K.; Tárraga, A.; Molina, P.; Veciana, J. (J. Am. Chem. Soc., 2005)

(untitled) - Li, S.; Zhang, D.; Xie, X.; Ma, S.; Liu, Y.; Xu, Z.; Gao, Y.; Ye, Y. (Sens. Actuators, B, 2016)

(untitled) - Braga, D.; Costa, A. L.; Grepioni, F.; Scaccianoce, L.; Tagliavini, E. (Organometallics, 1997)

(untitled) - Foster, N. R.; Grieves, G. A.; Buchanan, J. W.; Flynn, N. D.; Duncan, M. A. (J. Phys. Chem. A, 2000)

SAINT Software Reference Manual (SMART 5.0 and SAINT 4.0 for Windows NT) (Bruker Analytical X-ray Systems Inc., 1998)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. C: Struct. Chem., 2015)